OPTIMALISASI PENGGUNAAN BAHASA INDONESIA MELALUI KAMPANYE BAHASA DI MEDIA SOSIAL - Lili Sadeli; Eggie Nugraha (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
As a national language, Indonesian works as a symbol of national pride, a symbol of national identity, a unifying tool, and an interregional and intercultural communication tool. As a symbol of nationality, the Indonesian language is able to reflect socio-cultural values that we feel proud of as a symbol of national identity, we must uphold the Indonesian language next to our flag and country. Indonesian language must also be able to become a unifying tool for various ethnic groups who have different cultural and linguistic backgrounds. Indonesian has been proven to achieve harmony between ethnic groups in one nation, namely the Indonesian nation. In an effort to foster a sense of love for the homeland of the young generation, the problems that exist in the Young Generation include 1) using the Indonesian language for FKIP Unpas students; 2) the use of social media for PBSI PBSI FKIP Unpas students; 3) language campaign on social media. Based on the existing problems, it is necessary to have a language campaign as an effort to increase the existence of the Indonesian language and create a younger generation who will use the language. Keywords: Language, Indonesia, Campaign, Social Media.